Challenges Facing the Marketing of Scientific and Research Institutes - Sojkin Bogdan (Marketing of Scientific and Research Organizations, 2015)
This article presents the challenges that scientific research institutions face in terms of their marketing, which have been divided into two groups of those associated with internal marketing and those linked to external marketing. The most significant and important determinants that constitute challenges to both internal and external marketing were described. The key aspects of each of the identified challenges were indicated, as was their impact on the implementation of the marketing policy at institutions.